Insulin secretion after injuries of differing severity in the rat. - Frayn, K (1976)
The effects on insulin secretion of injuries of differing severity have been studied in the rat. The injuries used were dorsal scalds to 20% and 40% of the body surface area, and a 4-h period of bilateral hind-limb ischaemia. These injuries resulted in 48 h mortality rates of 0/10, 7/10 and 5/10 respectively. Rats were studied 1-5-2 h after scalding or removal of tourniquets. The blood glucose concentration was markedly raised after all these injuries, and the plasma insulin concentration was also raised, so that the insulin to glucose ratio in any group did not differ significantly from that in non-injured controls. Injection of glucose (0-5 g/kg i.v.) induced a rise in insulin concentration in all groups, although the insulin to glucose ratio after the lethal 40% scald was lower than in control rats. It was concluded that in the rat normal insulin secretion is maintained even after lethal injuries, although some suppression of the insulin response to exogenous glucose may occur. Insulin resistance is more important in the rat than impairment of insulin secretion even at an early stage after injury.